2009
DOI: 10.3233/jad-2009-1036
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Derived Atrophy of the Olfactory Bulb and Tract in Mild Cognitive Impairment and Alzheimer's Disease

Abstract: There is increasing histopathological evidence that the olfactory bulb and tract (OBT) is a primary focus of neurodegenerative changes in Alzheimer's disease (AD). Correspondingly, high-resolution magnetic resonance imaging revealed significant atrophy of the OBT in manifest AD. Whether these alterations are already present in mild cognitive impairment, the assumed preclinical stage of AD, has not been investigated yet. OBT volumes were assessed by manual tracing in 29 patients with mild cognitive impairment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 36 publications
1
51
0
2
Order By: Relevance
“…Importantly, ApoE ε4 carriers display higher tau pathology in the anterior olfactory nucleus (AON) in comparison to the ε4 negative individuals (Tsuboi et al, 2003). Finally, an MRI study demonstrated that pronounced olfactory bulb and fiber tract atrophy, a specific hallmark of AD (Mundinano et al, 2011), is present already very early in MCI patients (Thomann et al, 2009). Along the same line, it was shown that dystrophic neurites in the olfactory epithelium show high accumulations of paired helical filaments (PHFs; precursor elements of neurofibrillary tangles) and intracellular APP/Aβ in AD patients (Arnold et al, 2010).…”
Section: Olfactory-limbic Pathways and Admentioning
confidence: 99%
“…Importantly, ApoE ε4 carriers display higher tau pathology in the anterior olfactory nucleus (AON) in comparison to the ε4 negative individuals (Tsuboi et al, 2003). Finally, an MRI study demonstrated that pronounced olfactory bulb and fiber tract atrophy, a specific hallmark of AD (Mundinano et al, 2011), is present already very early in MCI patients (Thomann et al, 2009). Along the same line, it was shown that dystrophic neurites in the olfactory epithelium show high accumulations of paired helical filaments (PHFs; precursor elements of neurofibrillary tangles) and intracellular APP/Aβ in AD patients (Arnold et al, 2010).…”
Section: Olfactory-limbic Pathways and Admentioning
confidence: 99%
“…Compared to the olfactory tests the role of olfactory event-related potentials (OERPs) is considered useful in the diagnosis of AD (Morgan&Murphy, 2002). The results of olfactory tests are supported by functional imaging techniques (CT, MRI, PET) which show a reduced activation of the central olfactory structures (Wang et al, 2010), mainly on the right side (Kareken et al, 2001) and an atrophy of hippocampus (Jack et al, 1992;Yousem et al, 2001) and olfactory bulb (Thomann et al, 2009). Murphy et al (Murphy et al, 2003) studied olfactory function (odor threshold and odor identification) and volumetric MRI measures of mesial temporal areas (hippocampus, the parahippocampal gyrus and the amygdala) in patients with probable AD.…”
Section: The Role Of Olfactory Test In Alzheimer's Diseasementioning
confidence: 85%
“…Thus, altered cholesterol homeotasis could contribute to the development of olfactory dysfunction in sporadic AD. Pathologically, oxidative damage, the presence of Aβ plaque, and accumulation of phosphorylated tau as neurofilrillary tangles all have been documented in olfactory epithelium and olfactory bulbs of AD patients [44][45][46][47][48][49][50][51]. Previously we showed in olfactory bulb from cholesterol-fed rabbits that elevated levels of circulating cholesterol disrupted the blood-brain barrier [16], increased accumulations of cholesterol in endolysosomes of neurons in olfactory bulb originated from peripheral sources, and contributed to the development of AD-like pathology including synaptic loss, elevated Aβ production, and increased tau phosphorylation [7].…”
Section: Discussionmentioning
confidence: 99%